First manifestation of cardiovascular disease according to age and sex in a Mediterranean country - Ortega, Emilio; Genua, Idoia; Mata-Cases, Manel; Roqué, Mercè; Vlacho, Bogdan; Real Gatius, Jordi; Franch-Nadal, Josep; Mauricio, Didac (Frontiers in Cardiovascular Medicine, 2024)
Background Cardiovascular (CV) diseases are the most common cause of death worldwide. This study aimed to investigate the incidence and type of first CV event in a broad cohort of Spaniards, focusing on age and sex differences. Methods This was a retrospective study using the SIDIAP database. Subjects aged 30–89 years in 2010 were included. Individuals with prevalent CV disease or atrial fibrillation were excluded. Subjects were followed until the occurrence of a CV event, death, or the study end (December 2016). CV outcomes (coronary heart disease [CHD], cerebrovascular or peripheral artery disease and heart failure [HF]) during follow-up were analyzed. Clinical, anthropometrical, and laboratory data were retrieved from clinical records. Results Overall, 3,769,563 at-risk individuals (51.2 ± 15.2 years) were followed for a median of 7 years. The cumulative incidence of a first CV event was 6.66% (men vs. women, 7.48% vs. 5.90%), with the highest incidence (25.97%) among individuals >75 years. HF (29%) and CHD (28.8%) were the most common first events overall; in men it was CHD (33.6%), while in women it was HF and cerebrovascular disease (37.4% and 27.4%). In younger age groups, CHD was more prevalent, with HF in older age groups. Baseline CV risks factors conferred more risk in younger ages and differed between men and women. Conclusions The incidence and type of the first CV event in this Mediterranean region were significantly influenced by age and sex. This information is relevant for tailoring primary prevention strategies including the treatment of risk factors.